Communication Strategies Used by the English Teacher in Aviation Class - Rosidyana Rosidyana (Universitas Muhammadiyah Surakarta, 2020)
Problems in communication may happen not only with foreign language learners (EFL) learners but also with EFL teachers. Those problems happen wherefore the teachers inadequate of communicative competence. When teachers face difficulties in finishing their communication, and they initiate to use such gesture, it means they use communicative strategies. This study is aimed to find out the types of Communication Strategies (CSs) used by the English teacher during the teaching process at the Aviation class and to describe CSs which are dominantly used by the English teacher. By implementing Celce-Murcia’s taxonomy, the data was classified into five strategies and eleven sub-strategies. A qualitative research was used as the method in this study and the data was collected by doing observation and video recording the teacher in Aviation Course, Central Java. The result showed that five strategies were used by the English teacher included eleven sub-type strategies that appeared during teaching process. Based on the result, Filler (32,8%) was the highest number of strategies used by the teacher. Meanwhile, the least number of strategies used was retrieval (0,9%) and clarification request (0,9%). Thus, by conducting this study, the teacher was expected to use the best strategies to solve the communication problems during teaching and learning process.